Re-contextualizing Clay Figurines, Models, and Plaques from Iščali - Roßberger, Elisa (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Central questions about the function and meaning of the numerous figurines, models, and plaques surviving from late third and early second millennium Southern Mesopotamia remain unresolved. The two large temples and adjacent areas excavated in two seasons (1934–1936) at Iščali by the Diyala Expedition of the University of Chicago offer a rare chance to study contextual associations for a substantial number of these objects in sacred buildings and beyonds (Figure 1).